SPICE simulator for hybrid CMOS memristor circuit and system - Wang, Yuhao (2013)
Memristor is a two-terminal non-linear passive electrical device. After its recently successful fabrication, a variety of applications based on memristor have been explored, such as non-volatile memory, reconfigurable computing and neural network. However, one major challenge when designing hybrid CMOS memristor integrated circuit is the lack of SPICE-like simulator for design validation. Current approach is to describe memristor device with equivalent circuit, which is however extremely time-consuming for large scale design simulation due to additional modeling components. In this paper, a memristor SPICE simulator is introduced based on the recent new modified nodal analysis (MNA) framework, which can effectively support the non-conventional state variable such as doping ratio of memristor. As such, the memristor device can be stamped into state matrix similarly as one BSIM MOSFET. Compared with equivalent circuit simulation approach, our new MNA based approach exhibits 40x less simulation time for a 32×32 memristor crossbar circuit. A hybrid CMOS memristor circuit for classic conditioning training has also been studied by the developed SPICE simulator.